Association of Obesity with Adverse Maternal and Perinatal Outcome in Pregnant Women - Ruqqiya Azhar, Sundas Mushtaq, Mamoona Riaz, Humaira Aman, Rubina Qadeer, Sadia Aman (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Obesity is a current issue that has an impact on all healthcare services. Several prenatal and postpartum problems have maternal obesity as one of their risk factors. Many studies have shown that women with BMI≥30Kg/m2 experience increased incidence of intrapartum and perinatal complications. Objective: The objective of this study was to1determine the association of obesity with adverse maternal and perinatal outcome in pregnant women. Study design: Prospective cohort study. Setting: Obstetrics and Gynecology, Unit-II, Jinnah Hospital, Lahore. Material and methods: Total 232 pregnant women aged between 20-45 years presenting at ≥37 weeks of gestation. These patients were evaluated for obesity and two groups of patients were assimilated; those with obesity (BMI≥30 Kg/m2) and healthy controls (BMI 18.5-24.9 Kg/m2). Frequency of various fetomaternal outcome measures was noted and compared among these groups. A written informed consent was taken from each patient. Results: The age range from 20 years to 40 years with a mean of 28.40±5.30 years. Majority (n=210, 63.3%) of the patients were aged1between 20-30 years. The mean gestational age was 39.061.59 weeks. There were 157 (47.3%) primiparas and 175 (52.7%) multiparas. 187 (56.3%) patients were booked. Both the study groups1were comparable in terms1of mean age (p=0.613), mean gestational age (p=0.317), mean parity (p=0.168) and age (p=0.820), gestational age (p=0.071), parity (p=0.099) and booking status (p=0.580) groups distribution. The frequency of instrumental vaginal delivery (16.3% vs. 5.4%; p=0.001), cesarean delivery (36.1% vs. 10.2%; p<0.001), post-partum hemorrhage (10.8% vs. 1.8%; p=0.001), poor Apgar score (15.1% vs. 4.8%; p=0.002) & NICU admission (33.7% vs. 9.0; p<0.001) was significantly higher in obese women compared to non-obese controls. Conclusion: Maternal obesity was found to be associated with significantly higher frequency of instrumental vaginal delivery, cesarean delivery, post-partum hemorrhage, fetal macrosomia, poor Apgar score at 5.0 minutes & NICU admission regardless of patient’s age, gestational age, parity and booking status. Keywords: Maternal Obesity, Pregnancy, Maternal Complications, Fetal Complications